Cohort profile: the Maternal and Child Health and Nutrition in Acre, Brazil, birth cohort study (MINA-Brazil). Issue 2 (17th February 2020) - Cardoso, Marly; Matijasevich, Alicia; Malta, Maira Barreto; Lourenco, Barbara Hatzlhoffer; Gimeno, Suely G A; Ferreira, Marcelo U; Castro, Marcia C
Abstract : Purpose: Maternal and Child Health and Nutrition in Acre, Brazil (MINA-Brazil) is a longitudinal, prospective population-based birth cohort, set-up to understand the effects of early environmental exposures and maternal lifestyle choices on growth and development of the Amazonian children. Participants: Mother–baby pairs (n=1246) were enrolled at delivery from July 2015 to June 2016 in Cruzeiro do Sul, Acre, Brazil. Mothers of 43.7% of the cohort were recruited in the study during pregnancy from February 2015 to January 2016. Study visits took place during pregnancy, delivery, at 1 month, 6 months, 1 year and 2 years after delivery. In addition to clinical and epidemiological data, samples collected by the MINA-Brazil study include plasma, serum and extracted DNA from blood and faeces, which are stored in a biobank. Findings to date: Key baseline reports found a high prevalence of gestational night blindness (11.5%; 95% CI 9.97% to 13.25%) and maternal anaemia (39.4%; 95% CI 36.84% to 41.95%) at delivery. Antenatal malaria episodes (74.6% of Plasmodium vivax ) were diagnosed in 8.0% of the women and were associated with an average reduction in birth weight z-scores of 0.35 (95% CI 0.14 to 0.57) and in birth length z - scores of 0.31 (95% CI 0.08 to 0.54), compared with malaria-free pregnancies. At 2-year follow-up, data collection strategies combined telephone calls, WhatsApp, social media community and home visits to minimise losses of follow-up (retention rate of 79.5%). Future plans: A 5-year follow-up visit is planned in 2021 with similar interviews and biospecimens collection. The findings from this prospective cohort will provide novel insights into the roles of prenatal and postnatal factors in determining early childhood development in an Amazonian population.